PERBANDINGAN HASIL BELAJAR BAHASA INGGRIS ANTARA KELAS YANG MENERAPKAN PENDEKATAN KOMUNIKATIF DENGAN BANTUAN MULTIMEDIA DENGAN KELAS YANG YANG MENGGUNAKAN PEMBELAJARAN KONVENSIONAL - Amalia, Kania (2009)
This research project has been conducted to assess the influence of the application of the communicative approach aided with multimedia on the results of English language learning. It is also aimed at gaining information on the discrepancies between the results of learning of the class employing the communicative approach aided with multimedia (the experimental class) and those of the class employing conventional instruction (control class). The research project was experimental in nature and was conducted at SMKN 1 Cimahi. The samples were taken from two classes, one of the classes was considered as the experimental class, and the other was the control class. The research findings show that there is a significant degree of discrepancies between the results of learning of the two classes. The level of significance ^0; = 0.05 with a degree of independence of 66 yields a ttest greater than the ttable (5.4418 > 2.000). The application of the communicative approach which puts more stress on the language function relative to the grammatical aspects of the language was well conveyed by the teacher to the students. The learning media proves helpful to the teacher, in other words the use of media i.e. CD was highly welcomed by the students.